2008
DOI: 10.1614/wt-07-055.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Factors on Germination and Emergence of Swallowwort

Abstract: Swallowwort, a twining perennial of the Asclepiadaceae family, has become increasingly invasive in cultivated fields, orchards, fence rows, natural areas, and roadsides of some provinces in Iran. The ability of this weed to establish and develop from seed was studied in laboratory and greenhouse experiments. Optimum germination temperature was 25 C. Germination did not occur at ≤ 15 C either in dark or light. In temperature fluctuation experiments, maximum germination occurred at 30/22 C, but light fluctuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…This indicates that the germination rate increased with increasing the water energy, or that irrigation with microwave treated water in a higher power. This may be because the excess kinetic energy of the treated water increased the conversion of seed starch into sugars that agree with (Pahlevani et al, 2008). Around 90 s exposure duration at 30 w and 50w power were observed as the best value for seedling enzymes.…”
Section: Resultssupporting
confidence: 55%
“…This indicates that the germination rate increased with increasing the water energy, or that irrigation with microwave treated water in a higher power. This may be because the excess kinetic energy of the treated water increased the conversion of seed starch into sugars that agree with (Pahlevani et al, 2008). Around 90 s exposure duration at 30 w and 50w power were observed as the best value for seedling enzymes.…”
Section: Resultssupporting
confidence: 55%
“…(2008) reported that alternating temperatures can result in a higher seed germination rate than that seen at constant temperatures for Hibiscus trionum . Whereas, Ellis and Barrett (1994) and Pahlevani et al. (2008) did not find any clear effect of alternating temperature within the optimum range for seed germination in Lens culinaris and Cynanchum acutum , respectively.…”
Section: Resultsmentioning
confidence: 69%
“…Physiological processes in some weeds are negatively affected by soil salinity (DiTommaso, 2004;Chauhan & Johnson, 2008b). High salt concentration inhibits the germination of many weed seeds and it ultimately leads towards death (Koger et al, 2004;Pahlevani et al, 2008;Nemati et al, 2011), with some exceptions as a few types of weed seeds show tolerance to high salt concentrations (Chauhan & Johnson, 2008c). Seed burial depth also affects its germination and seedling emergence (Koger et al, 2004;Mennan & Ngouajio, 2006).…”
Section: Introductionmentioning
confidence: 99%